Chemical constituents of Cycas aenigma - Ng, Vincent Antonio S. (Animo Repository, 2015)
Chemical investigation of Cycas aenigma, a plant endemic to the Philippines, led to the isolation of a rare neolignan, 2-[2-hydroxy-5-(3-hydroxypropyl)-3-methoxyphenyl]-1-(4-hydroxy-3-methoxyphenyl)propane-1,3-diol (1), pinoresinol (2), and fatty alcohols (3) from the leaflets; and triglycerols (4), and a mixture of β-sitosterol (5a) and stigmasterol (5b) from the petiole and rachis. The structure of 1 was elucidated by extensive 1D and 2D NMR spectroscopy, while those of 2-5b were identified by comparison of their 1H and/or 13C NMR data with literature data. © 2015 Vincent Antonio S. Ng et al.